2012
DOI: 10.3390/molecules17089803
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Activity of Lavender Oil on Transient Focal Cerebral Ischemia in Mice

Abstract: The air-dried aerial parts of Lavandula angustifolia Mill, a traditional Uygur herbal drug, is used as resuscitation-inducing therapy to treat neurodisfunctions, such as stroke. This study was designed to assess the neuroprotective effects of lavender oil against ischemia/reperfusion (IR) injury in mice. Focal cerebral ischemia was induced by the intraluminal occlusion method with a nylon string. The neurodysfuntion was evaluated by neurological deficit and the infarct area was showed by 2,3,5-triphenyltetrazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 42 publications
3
45
0
3
Order By: Relevance
“…Others have shown that chemicals with protective effects on cerebral injury reverse damage to mitochondrial membrane potential. 5,6 It is possible that the protective effect of ischaemic postconditioning is also related to improvements in mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown that chemicals with protective effects on cerebral injury reverse damage to mitochondrial membrane potential. 5,6 It is possible that the protective effect of ischaemic postconditioning is also related to improvements in mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Antioxidants have been shown to have therapeutic effects on ischaemia/reperfusion brain injury, suggesting that oxidative stress has an active role in modulating neuronal destiny. [4][5][6] In addition, other neurological disorders (including neurodegenerative diseases and traumatic brain injury) are related to oxidative stress. 7,8 The crucial feature of oxidative stress is overproduction of reactive oxygen species (ROS) resulting from disruption to the equilibrium between ROS formation and clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Restitution of blood flow with reperfusion sustains renal injury through further generation of ROS (Bidmon et al, 2012). ROS are capable of reacting with proteins, lipids, and nucleic acids leading to protein denaturation, lipid peroxidation, and DNA damage (Bidmon et al, 2012;Wang et al, 2012a). Many antioxidants have been the focus of studies for developing strategies for use in I/R therapy (Mahfoudh Boussaid et al, 2007;Wang et al, 2012a;Aydogan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…ROS are capable of reacting with proteins, lipids, and nucleic acids leading to protein denaturation, lipid peroxidation, and DNA damage (Bidmon et al, 2012;Wang et al, 2012a). Many antioxidants have been the focus of studies for developing strategies for use in I/R therapy (Mahfoudh Boussaid et al, 2007;Wang et al, 2012a;Aydogan et al, 2013). Along with others, we have shown that the antioxidant molecule, melatonin, has a significant protective action against renal damage that occurs during I/R injury (Aktoz et al, 2007;Ersoz et al, 2009;Hadj Ayed Tka et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the regular use of lavander oil in skin preparations could suppress the aging effects of sunlight on the skin. Wang et al [47] found that treatment with lavander oil significantly decreased neurological deficit scores, infarct size, the levels of malondialdehyde, carbonyl and reactive oxygen species (ROS), and attenuated neuronal damage, upregulated antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) activities. These results suggested that the neuroprotective effects of lavander oil against cerebral ischemia/reperfusion injury in mice may be attributed to its antioxidant effects [47].…”
Section: Salvia Officinalis Salvia Officinalis L (Common Sagementioning
confidence: 99%